Development of Educational Board Games to Increase Knowledge of Environmental Care Integrated with QR Codes and Applications - Nadine Margaretha Octaviola; Khusnul Khotimah; Esti Untari (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2024)
This study aims to develop a board game as a learning media that provides environmental awareness education for elementary school children. To follow the era of society 5.0, this board game is developed with technological advances in the form of QR codes and applications and meets the quality of interesting learning media. With the existence of this game-based learning media, it will increase students' knowledge of environmental awareness. To determine the feasibility, effectiveness, and attractiveness of the results of the development of board game learning media integrated with QR codes and applications. This study uses the Research and Development (RnD) method. This research model uses ADDIE, namely analysis, design, development, implementation, and evaluation. The data collection techniques used are questionnaires and tests in the form of quantitative and qualitative descriptive data. Board games were declared valid by the three experts as evidenced by the results (1) material experts had a percentage of 90%, (2) media experts had a percentage of 98% (3) teachers had a percentage of 100%. After being declared valid, the media was tested on grade III students of SDN Bareng 01 Malang City. Based on the results of the pretest t-test analysis, the average was 69 and the post-test was 91. The conclusion that can be drawn from this study shows that there is a significant influence of board games so that it can increase the environmental awareness knowledge of students at SDN Bareng 01 Malang City.